Garbage Citizenship : Vital Infrastructures of Labor in Dakar, Senegal - Fredericks, Rosalind (Book collections on Project MUSE., 2018)
Rosalind Fredericks traces the volatile trash politics in Dakar, Senegal, to examine urban citizenship in the context of urban austerity and democratic politics, showing how labor is a key component of infrastructural systems and how Dakar's residents use infrastructures as a vital tool for forging collective identifies and mobilizing political action.